(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2023)
The wave of disinformation that marked recent years led to the emergence of new conceptual categories, such as ‘post truth’. However, it also generated forms of reaction to the phenomenon, such as fact-checking, a journalistic genre that has recently established itself worldwide. The first theoretical hypothesis of this paper postulates that the success of fact-checking can be interpreted as a contemporary return to the ideals of so-called ‘modern’ journalism. These ideals emerged between the 19th century and the first decades of the 20th century and were incorporated within journalism through the principles of the Enlightenment and scientific modernity: objectivity, impartiality, reliance on data and evidence (until they dispersed, in the postmodern turn, with the occurrence of the web). This paper analyses the potentials and limits of this “old-new” model of journalism, using examples from leading international fact-checking projects. Regarding the limits, it will be discussed how practicing fact-checking without adopting a partial point of view is unachievable. Additionally, our analysis will also shed light on how, upon closer inspection, the category of disinformation’ itself turns out to be ambiguous. As for the potentials, we will examine best practices that allow a scrutiny of journalistic narratives on facts, considering examples of ‘good fact-checking’ that does not claim absolute objectivity. We develop the argument that good fact-checking can help to pursue a new model of objectivity and scientificity, based on assumptions such as the falsifiability of statements, the replicability of experiments, and the delimitation of the context of analysis. Finally, we argue that this objectivity should be seen as a form of open rationality rather than a new ‘dogmatism of facts’.